Study of the Characteristics and Oxidative Stability of a Mixture of Avocado Oil and Coconut Oil - Lucia Saraswati; Aisman; Daimon Syukri (Postgraduate, University of Mataram, 2025)
This study aimed to evaluate the effect of blending avocado oil and coconut oil on the resulting physicochemical characteristics. Oil blends were prepared in six ratios of avocado oil to coconut oil (100:0; 80:20; 60:40; 40:60; 20:80; 0:100 v/v). The analyzed parameters included peroxide value, free fatty acids (FFA), iodine value, saponification value, fatty acid profile (GC-FID), and color test. The results showed that the blend in treatment C, with a ratio of avocado oil to coconut oil (60:40 v/v), yielded a peroxide value of 9.23 ± 0.32 meqO₂/kg, FFA of 0.73 ± 0.17%, iodine value of 47.33 ± 0.71 g I₂/100 g, and saponification value of 202.33 ± 0.54 mg KOH/g. The fatty acid profile was dominated by oleic acid, lauric acid, and palmitic acid. This blend produced a more diverse fatty acid profile and exhibited better oxidative stability compared to pure avocado oil. Therefore, blending avocado oil and coconut oil at a ratio of 60:40 v/v resulted in an oil product with a more varied fatty acid composition and improved oxidative stability compared to pure avocado oil.